MARIE PONSOTS EVER-FIXÉD MARK. - YEZZI, DAVID (Sewanee Review)
The article explores the work of U.S. poetry and essayist Marie Ponsot. She published a half dozen books of poetry, including "True Minds" and "Easy." Ponsot emerged during the first wave of pioneering women Modernists in the country. Themes of her poetry are discussed, including violence, love, death and music.